Square Shaped MEMS Capacitive Pressure Sensors for Biological Applications - ., Suman; Bhatia, Deepak (ECS transactions, 2022)
The focus of this study is on mathematical modelling analysis and simulation of a micromechanical system based on a capacitive pressure sensor with a square diaphragm of 500 μm × 500 μm. The mechanical operation of the suggested device under the impact of a uniform pressure range employing different materials on the same arrangement is the subject of this research. The principle, design and comparative analysis of several MEMS materials are covered in this work. The deflection of the capacitive pressure sensor of roughly 0.285 μm and 30.36 pF, as well as the change in the capacitance value, are used to evaluate the device's performance. At a maximum pressure of 20 kPa at room temperature, the sensor's sensitivity is 56.24× 10 -6 pF/pa, and the sensor’s response time is also reduced under static and dynamic loading circumstances. It can be seen that graphene materials have linear, stable, and repeatable properties when subjected to a uniform pressure range.